The Urgency of Law Enforcement Against Overclaiming Skincare Products on Social Media in the Perspective of Law Number 8 of 1999 concerning Consumer Protection - Aisyah, Nisrina Prili; Susanto, Arvina Aulia; Febijayanti, Ni Ketut Andari; Tamim, Raisya Anidya Meilvira (AL-SULTHANIYAH, 2026)
The skincare industry is growing rapidly in the digital era, particularly through promotions on social media, which often utilize marketing strategies involving excessive claims. This phenomenon raises legal issues because it can mislead consumers and violate their rights. This study aims to analyze the urgency of law enforcement against the practice of overclaiming skincare products, focusing on Law Number 8 of 1999 concerning Consumer Protection. The research method used is normative juridical, with a statutory approach, legal literature, and case analysis. The results show that although regulations explicitly prohibit misleading advertising, law enforcement still faces obstacles, including weak oversight in the digital realm and low consumer legal literacy. Therefore, strengthening regulations, optimizing the role of supervisory institutions, and increasing consumer awareness are crucial aspects in realizing effective legal protection. This study concludes that consistent and adaptive law enforcement is an urgent need to address the dynamics of skincare product marketing in the digital era.